Phospholipid vesicles interfere with the binding of antibody fragments to the light chain of factor VIII - Lewis, Deborah A.; Bovenschen, Niels; Mertens, Koen; Voorberg, Jan; Ortel, Thomas L. (Thrombosis and Haemostasis, 2005)
Factor VIII binds to phospholipid membranes through the C2 domain (S2173-Y2332). Residues M2199, F2200, L2251, L2252, V2223, W2313 and V2314 at the tips of β-hairpins and loops are thought to contribute to phospholipid membrane binding. Similarly, residues in the C2 domain of the homologous protein factor V form a phospholipid binding site, but residues in the A3 and C1 domains are also thought to contribute to membrane binding. Phage display technology was previously used to isolate factor VIII light chain specific single-chain variable domain fragments (scFv) from patients with factor VIII inhibitors. Phospholipid vesicles inhibited the binding of factor VIII to scFvsWR1 and WR16 (epitope: E2181-M2199) with half saturation values of 23 and 47 μM respectively. The single point mutant F2200A factor VIII light chain bound to WR1 and WR16 with a much lower affinity than wild type protein suggesting that residue F2200 is also included in the epitopes of these scFvs. Binding of factor VIII to C2-specific scFvsWR13 and EL14 (epitope: K2207-M2321) was not inhibited by phospholipid vesicles. Consistent with this, F2200A factor VIII light chain bound to these scFvs with the same affinity as the wild type protein. However, phospholipid vesicles also inhibited the binding of factor VIII to the A3-C1-specific scFvs KM36 (epitope: Q1778-D1840) and KM38 (epitope: S1690-N1777 and/or V1841-N2172) with half saturation values of 84 and 165 μM, respectively, suggesting that the A3 and/or C1 domains may contribute to membrane binding of the cofactor.
Keywords: Factor VIII; phospholipids; antibody